2017
DOI: 10.1016/j.rmed.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of asthmatics with detectable IL-32γ in induced sputum

Abstract: The level of IL-32γ in induced sputum may be associated with asthma severity and related with higher risk of asthma exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…IL-32 has increasingly been suggested as a key player in the pathophysiology of asthma. In asthma, the airway presence of IL-32γ is negatively correlated with the forced expiratory volume in 1 s (FEV1) and positively correlated with the annual exacerbation rate [ 60 ]. In that study, the authors concluded that the increased IL-32γ level in the induced sputum samples correlated with an increased risk of asthma exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…IL-32 has increasingly been suggested as a key player in the pathophysiology of asthma. In asthma, the airway presence of IL-32γ is negatively correlated with the forced expiratory volume in 1 s (FEV1) and positively correlated with the annual exacerbation rate [ 60 ]. In that study, the authors concluded that the increased IL-32γ level in the induced sputum samples correlated with an increased risk of asthma exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, IL-32q has been suggested to play an intracellular modulatory role in breast cancer cells (56,59). On the other hand, a study conducted on asthma patients showed a lower IL-32g compared to healthy controls (37) as well as rIL-32g that showed a negative regulatory effect in an asthma mouse model (14). However, this report did not consider the behavior of the IL-32q isoform.…”
Section: Discussionmentioning
confidence: 81%
“…Patients were enrolled from Soonchunhyang University Bucheon Hospital (11). Asthma was diagnosed by physicians based on the Global Initiative for Asthma guidelines (12).…”
Section: Study Participantsmentioning
confidence: 99%